Factors determining the development of SMEs in Jaffna District. - Sathana, V.; Velnampy, T.; Rajumesh, S. (University of Jaffna, 2018)
SMEs play prominent role in any economy through generating employments, contributing to Gross Domestic Product (GDP), embarking innovations and stimulating of other economic activities (ESBA, 2011). This sector is said to be the backbone for all developed and developing nations. SME sector is envisaged to contribute to transform lagging regions into emerging regions of prosperity (Ministry of Industry and commerce, 2015). End of the local war in Sri Lanka, SMEs in Jaffna district have been facing complex environment and the struggling to develop. At the same time SMEs have plentiful opportunities to develop in the Jaffna district. There is need to identify the determining factors of development of SMEs. Financial development, growth and customer development were already investigated and empirically tested with the name of financial performance and market performance in SMEs. Organization development explains one of the dimension as the employee development which was not empirically analyzed in SMEs. Sustainable development reveals the social development which is also unique concept for the SMEs. However these combination of development concept for SMEs has still not been developed and empirically investigated in the SMEs in Jaffna district, which is the gap of the study. There is need to study how these SMEs have been growing and developing by managing external environment challenges and the internal environment weakness. Therefore, the main aim of this study is to identify the determining factors of development of SMEs in Jaffna district.